Adaptasi dan Validasi Instrumen Career Adapt-Abilities Scale (CAAS) Versi Bahasa Indonesia untuk Mengukur Kesiapan Karier Siswa SMK - Widyawati, Mareta Lusiana; Istiyono, Edi; Setiawati, Farida Agus (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to adapt the Career Adapt-Abilities Scale (CAAS) into Indonesian language to suit the context of vocational high school (SMK) students in Indonesia. The purpose is to develop a reliable and valid instrument for assessing students’ career readiness, considering the linguistic and cultural characteristics of the local educational setting.Method – The adaptation process followed established guidelines, involving translation, expert validation, and field testing with 276 students from grades XI and XII in SMK Ponorogo. Content validity was assessed using Aiken’s V index, while construct validity was evaluated through Exploratory Factor Analysis (EFA) using JASP software. Internal consistency was examined using Cronbach’s Alpha. Findings – The results showed that 21 out of 24 items had Aiken’s V values ? 0.60, indicating good content validity. EFA revealed a new three-factor structure Concern, Curiosity, and a merged Control/Confidence factor which differed from the original four-factor model. The adapted instrument demonstrated high internal consistency with a Cronbach’s Alpha of 0.895. These findings suggest that the Indonesian version of CAAS is a valid and reliable tool for measuring career adaptability among SMK students. Research Implications – The factor structure shift highlights contextual differences that should be considered in instrument adaptation. This study was limited to students from one district (Ponorogo), so broader sampling across different regions and school types is recommended to enhance generalizability. Further studies using Confirmatory Factor Analysis (CFA) are also encouraged to verify the factor stability of the Indonesian CAAS version and to explore its predictive validity related to students’ employability outcomes.